Star wars the mandalorian (2022): season two, part one ebook - Barnes, Rodney (Star Wars: The Mandalorian (2022), 2024)
Collects Star Wars: The Mandalorian Season 2 (2023) #1-4. What secrets does the child hold? The Mandalorian continues his long journey with the child called Grogu, trying to return the foundling to the Jedi — but the galaxy is a dangerous place in the wake of the Galactic Empire's collapse, and new enemies lurk on every planet. Thankfully, allies both familiar and unexpected will aid them on their travels! But is there another Mandalorian operating on Tatooine? Can Din Djarin grant safe passage for a Frog Lady and her precious eggs with an ever-hungry Grogu on board? Can they both survive encounters with remnants of Imperial forces, spider-like creatures and a krayt dragon?